Primeiro registro de Lustrochernes Beier, 1932 (Pseudoscorpiones: Chernetidae) associado a Mallodon spinibarbis (Linnaeus, 1758) (Coleoptera: Cerambycidae) no sudeste do Brasil - André R. Marra; Heitor Z. Fischer (Entomological Communications, 2023)
Four specimens of Mallodon spinibarbis (Linnaeus, 1758) (Coleoptera: Cerambycidae) was collected in a tamarind tree (Tamarindus indica L.), in Sorocaba, São Paulo, Brazil, and one of them carried under its elytra four Lustrochernes sp. (Pseudoscorpiones: Chernetidae). Among 26 species of this pseudoscorpions' genus in the world, seven are reported in Brazil, and their occurrence is mentioned only in a few states. Phoresia involving species of Lustrochernes Beier, 1932 in Brazil was mentioned only in Amazonas and Roraima's states, involving this cerambicide and species from other families. This paper reports Lustrochernes sp. as a phoront of M. spinibarbis for the first time in São Paulo’s state and thus contributes to increase the occurrence of this association.